PAF and Haematopoiesis. I. 5-Fluoro-Uracil Induces PAF Production in Haematopoietic Organs of Rats - Y. Denizot; V. Praloran (Mediators of Inflammation)
Haematopoietic organs of rats were examined for the presence of platelet-activating factor (PAF) and acetylhydrolase before and after treatment with 5-fluoro-uracil (5-FU) (200 mg/kg) a chemotherapeutic compound with apoptotic effects. PAF was reported in thymus, spleen and femoral bone marrow of rats with or without 5-FU. Although acetylhydrolase activity in organs was not affected by 5-FU treatment, elevated levels of PAF were observed in thymus and spleen. For the first time PAF is reported in haematopoietic organs of rats, strengthening in vitro data suggesting its role in the apoptotic processes in thymus, in the modulation of the immune response, and in the regulation of haematopoiesis.